Photosystem II antenna complexes CP26 and CP29 are essential for nonphotochemical quenching in Chlamydomonas reinhardtii. (8th December 2019) - Cazzaniga, Stefano; Kim, Minjae; Bellamoli, Francesco; Jeong, Jooyoen; Lee, Sangmuk; Perozeni, Federico; Pompa, Andrea; Jin, EonSeon; Ballottari, Matteo
Abstract: Photosystems must balance between light harvesting to fuel the photosynthetic process for CO2 fixation and mitigating the risk of photodamage due to absorption of light energy in excess. Eukaryotic photosynthetic organisms evolved an array of pigment‐binding proteins called light harvesting complexes constituting the external antenna system in the photosystems, where both light harvesting and activation of photoprotective mechanisms occur. In this work, the balancing role of CP29 and CP26 photosystem II antenna subunits was investigated in Chlamydomonas reinhardtii using CRISPR‐Cas9 technology to obtain single and double mutants depleted of monomeric antennas. Absence of CP26 and CP29 impaired both photosynthetic efficiency and photoprotection: Excitation energy transfer from external antenna to reaction centre was reduced, and state transitions were completely impaired. Moreover, differently from higher plants, photosystem II monomeric antenna proteins resulted to be essential for photoprotective thermal dissipation of excitation energy by nonphotochemical quenching. Abstract : The functional role of the Photosystem II monomeric antenna complexes CP29 and CP26 was investigated in Chlamydomonas reinhardtii generating single and double mutants by CRISPR‐Cas9 genome editing demonstrating their key role in non‐photochemical quenching of both Photosystem I and II.